Logistics Selection Using AHP and Super Decisions Software - Mubarok, Akhmad Yasir; Ristiyaningsih, Ristiyaningsih; Purnamasari, Pupung (Talent: Journal of Economics and Business, 2024)
The current trend of companies is to hand over their Logistics activities to third parties, so that they can focus more on their fields. The choice of Logistics services is also very crucial for the company, because it determines the reputation of a company in the eyes of customers. This study aims to evaluate the decision to choose the best logistics service that is used to meet customer needs, especially in terms of shipping goods. To do this, the AHP (Analytical Hierarchy Process) method is used to make decisions on the use of Logistics based on predetermined criteria, namely Cost, Services, and Reliability. There are five alternatives that are taken, namely using their own fleet, using instant delivery services such as Grab Express and GoBox or using third party Logistics services such as Trimulya Logistics and Herona Express. In this study, the calculation process uses the tools of the Super Decisions Software. The results of this study indicate that the criteria that have the highest weight are Services with a value of 0.50536 and the alternative that has the highest weight is Trimulya Logistics with a value of 0.363531.